Synthetic microbe communities provide internal reference standards for metagenome sequencing and analysis - Simon A. Hardwick (Nature Portfolio, 2018)
Complex microbial communities pose a challenge to metagenomic analysis. Here the authors develop ‘sequins’, internal DNA standards that represent a synthetic community of artificial genomes.